DAMPAK PERUBAHAN TARIF PAJAK BADAN TERHADAP TAX AVOIDANCE DI INDONESIA - Oktavianie, Rian (UNIB Press, 2019)
This study aims to purpose the impact of changes in corporate tax rates to tax avoidance in Indonesia. The samples are manufacturing companies listed in Indonesia Stock Exchange which published reporting statement during 2007-2014.The sampling technique used is purposive sampling and obtained 25 companies with data processed about 200. The independent variable in this study are tax avoidance before tax rates changes (X1) and the tax avoidance after tax rates changes (X2), while the dependent variable is tax avoidance (Y). The analysis used descriptive statistical anaylsis, test Kolmogrov-Smirnov, and different t-test with used paired sample test as tool. T-test used to know the level of differences tax avoidance between before and after tax rates changes tax with apply in corporate.Results from this study indicate that there are differences in tax avoidance before and after the change in corporate tax rates. Tax avoidance as measured by the Cash ETR and Current ETR shows that after changes in corporate tax rate higher tax avoidance or tax increases. Whereas measurement by Effective Tax Rates and Total Book Tax Differences shows that there are differences of tax avoidance lesser or reduced after the change in corporate tax rates.